Local application of osteoprotegerin-chitosan gel in critical-sized defects in a rabbit model - Jayash, S.N.; Hashim, Najihah Mohd; Misran, Misni; Baharuddin, Nor Adinar (PeerJ, 2017)
Background. Osteoprotegerin (OPG) is used for the systemic treatment of bone diseases although it has many side effects. The aim of this study was to investigate a newly formulated OPG-chitosan gel fort local application to repair bone defects. Recent studies have reported that immunodetection of osteopontin (OPN) and osteocalcin (OC) can be used to characterise osteogenesis and new bone formation. Method The osteogenic potential of the OPG-chitosan gel was evaluated rabbits. Critical-sized defects were created in the calvarial bone, which were either left unfilled (control; group I), or filled with chitosan gel (group II) or OPG-chitosan gel (group III), with rabbits sacrificed at 6 and 12 weeks. Bone samples from the surgical area were decalcified and treated with routine histological and immunohistochemical protocols using OC, OPN, and cathepsin K (osteoclast marker) antibodies. The toxicity of the OPG-chitosan gel was evaluated by biochemical assays (liver and kidney function tests). Results. The mean bone growth in defects filled with the OPG-chitosan gel was significantly higher than those filled with the chitosan gel or the unfilled group (p < 0.05). At 6 and 12 weeks, the highest levels of OC and OPN markers were found in the OPG-chitosan gel group, followed by the chitosan gel group. The number of osteoclasts in the OPG-chitosan gel group was lower than the other groups. The results of the liver and kidney functional tests indicated no signs of harmful systemic effects of treatment. In conclusion the OPG-chitosan gel has many characteristics that make it suitable for bone repair and regeneration, highlighting its potential benefits for tissue engineering applications.